\[I=\int x^3 dx\] \[let \space x=\red{\cos\theta}\Rightarrow dx=-\sin\theta d\theta\] \[\Rightarrow I=-\int\cos^3\theta\sin\theta d\theta\] \[=\dfrac{-1}{2}\int (\cos 2\theta\cos\theta+\cos\theta)\sin\theta d\theta\] \[=\dfrac{-1}{2}\int\cos 2\theta\sin\theta\cos\theta d\theta - \dfrac{1}{2}\int\cos\theta\sin\theta d\theta\] \[=\dfrac{-1}{4}\int\cos 2\theta\sin 2\theta d\theta - \dfrac{1}{4}\int\sin 2\theta d\theta\] \[= \dfrac{-1}{8}\int\sin 4\theta d\theta - \dfrac{1}{4}\int\sin 2\theta d\theta\] \[=\dfrac{-1}{8}\times\dfrac{-\cos 4\theta}{4} - \dfrac{1}{4}\times\dfrac{-\cos 2\theta}{2}+c\] \[=\dfrac{\cos 4\theta}{32}+\dfrac{\cos 2\theta}{8}+c\] \[=\dfrac{2\cos^2 2\theta - 1}{32}+\dfrac{2\cos^2\theta-1}{8}+c\] \[=\dfrac{2(2\red{\cos^2\theta}-1)^2 - 1}{32}+\dfrac{2\red{\cos^2\theta}-1}{8}+c\] \[=\dfrac{2(2\red{x^2}-1)^2 - 1}{32}+\dfrac{2\red{x^2}-1}{8}+c\] \[=\dfrac{2(4x^4+1-4x^2) - 1}{32}+\dfrac{2x^2{-1}}{8}\blue{+c}\] \[= \dfrac{8x^4\blue{+2}-8x^2 \blue{-1}}{32}+\dfrac{2x^2\blue{-1}}{8}+c\] \[= \red{\dfrac{8x^4}{32}}\blue{+\dfrac{1}{32}}\red{-\dfrac{8x^2}{32}+\dfrac{2x^2}{8}}\blue{-\dfrac{1}{8}+c}\] \[= \red{\dfrac{x^4}{4}}\cancel{\red{-\dfrac{x^2}{4}}}\cancel{\red{+\dfrac{x^2}{4}}}+\blue{C}\] \[= \red{\dfrac{x^4}{4}}+\blue{C}\]
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
What about hyperbolic trigonometric substitution: x=sinhθ?
Log in to reply
I=∫x3dx let x=sinhθ⇒dx=coshθdθ ⇒I=∫sinh3θcoshθdθ =21∫coshθsinh2θsinh2θcoshθdθ =21∫sinh2θsinh2θdθ =41∫sinh2θ(cosh2θ−1)dθ =41∫sinh2θcosh2θdθ−41∫sinh2θdθ =81∫sinh4θdθ−41∫sinh2θdθ =81×4cosh4θ−41×2cosh2θ+c =322cosh2θ−1−82sinh2θ+1+c =322(2sinhθ2+1)2−1−82sinh2θ+1+c =322(2x2+1)2−1−82x2+1+c =328x4+8x2+2−1−82x2+1+c =328x4+328x2+321−82x2−81+c =4x4+4x2−4x2+C =4x4+C
Log in to reply
Beautiful. Now what about integration by parts? ∫x3dx=∫x⋅x2dx?
;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;) ;)
Log in to reply